Nanocrystalline Mn-Zn-ferrite by novel oxalato-hydrazinated complex method - Kanade, K. G.; Amalnerkar, Dinesh P.; Potdar, H. S.; Kale, B. B. (Materials Chemistry and Physics, 2009)
We report here for the first time the synthesis of technologically important ferrite, using a metal oxalato-hydrazinate (MOH) complex method. The MOH complex of iron-manganese-zinc was synthesized at room temperature using the precursors, ferrous ammonium sulphate, manganese acetate and zinc acetate. Thermo-gravimetric studies of MOH intermediate showed complete phase formation of MnZnFe(2)O(4) at 280 degrees C. XRD data showed the formation of single phase cubic spinel MnZnFe(2)O(4). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) demonstrate the spherical shape particle morphology. TEM images indicated the particle size of ferrite powder in the range of 20-36 nm. Magnetization of synthesized nano-sized Mn(0.69)Zn(.0.19)Fe(2.12)O(4) was observed coercive force (H(c)) at 127.82 Oe with a saturation magnetization (M(s)), 34.5 emu g(-1) using vibrating sample magnetometer (VSM) at room temperature. Mossbauer study of nano-sized ferrite powder showed super-paramagnteic behavior. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic materials; Mn-Zn-ferrite; Nanostructures; Optical properties

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures